Fauna of mantids and orthopterans (Insecta: Mantodea, Orthoptera) of the Mordovia State Nature Reserve, Russia - ALEXANDER B. RUCHIN; ANDREY P. MIKHAILENKO (Society for Indonesian Biodiversity, 2018)
Ruchin A, Mikhailenko AP. 2018. Fauna of mantids and orthopterans (Insecta: Mantodea, Orthoptera) of the Mordovia State Nature Reserve, Russia. Biodiversitas 19: 1194-1206. The data on the distribution and habitat confinement of one Mantodea species and 44 Orthoptera species in the Mordovia State Nature Reserve are given. Of these, one species of Orthoptera (Calliptamus italicus) is recorded for the first time for the Mordovia State Nature Reserve, four species (Mantis religiosa, Phaneroptera falcata, Conocephalus fuscus, Tettigonia caudata) are recently penetrated, one species (Conocephalus fuscus) is reported in the Republic of Mordovia for the first time. In the fauna of mantids and orthopterans of the Mordovia Reserve, three ecological groups were identified: polytopic, not confined to certain biotopes (14 species), hygrophilous representatives of intrazonal habitats (5 species) and xerophiles. Among the latter, there are species of extrazonal habitats (13 species) and confined to dry pine forests (7 species). The steppe group was not represented. For the three key habitats with the largest number of identified species, brief botanical descriptions are given. Factors influencing the species composition and current state of fauna of mantises and orthopterans of the Mordovia Reserve are discussed, and measures are proposed for the conservation of vulnerable species.